Current Controlled Differential Difference Current Conveyor Transconductance Amplifier and Its Application as Wave Active Filter. (28th February 2013) - Pandey, Neeta; Kumar, Praveen; Choudhary, Jaya
Abstract : This paper proposes current controlled differential difference current conveyor transconductance amplifier (CCDDCCTA), a new active building block for analog signal processing. The functionality of the proposed block is verified via SPICE simulations using 0.25 μ m TSMC CMOS technology parameters. The usefulness of the proposed element is demonstrated through an application, namely, wave filter. The CCDDCCTA-based wave equivalents are developed which use grounded capacitors and do not employ any resistors. The flexibility of terminal characteristics is utilized to suggest an alternate wave equivalents realization scheme which results in compact realization of wave filter. The feasibility of CCDDCCTA-based wave active filter is confirmed through simulation of a third-order Butterworth filter. The filter cutoff frequency can be tuned electronically via bias current.